Beneath the 12-mile reef - Webb, Robert, 1903-1990; Bassler, Robert, 1903-1975; Bezzerides, A. I. (Albert Isaac), 1908-2007; Wagner, Robert, 1930-; Twentieth Century-Fox Film Corporation ([Los Angeles, Calif.] : Twentieth Century-Fox Film Corporation, 1953)
A story that takes place in the Gulf of Mexico, on the west coast of Florida, in which a family of sponge fishermen of Greek origin, to obtain greater profits, decide to go fishing on the island of 12 miles, a place very dangerous, but also very profitable, due to the large size of the sponges that can be obtained there. The father, Mike, gets a good catch, but some Englishmen, sponge fishermen in turn, who think they have more rights than the Greeks to fish in the waters around the island, assault him and steal all the sponges. Mike persists in fishing in the fearsome waters which, after a fortuitous accident, will lead to his death. The English, led by Thomas, will continue to plunder Tony, Mike's son, a situation that will be aggravated when he escapes with Winie, the daughter of the English chief, after falling in love with each other. --
Robert Wagner, Terry Moore, Gilbert Roland, J. Carrol Naish, Richard Boone, Angela Clarke, Peter Graves, Richard Boone, Jay Novello, Jacques Aubuchon.
Editor, William Reynolds ; music, Bernard Henmann ; director of photography, Edward Cronjager.
In Spanish.
Best Cinematography Color nomination - Oscars
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 4, 2022)
Keywords: Sponge fisheries -- Florida -- Drama; Vendetta -- Drama; Motion pictures; Action and adventure films; Feature films; Fiction films; Streaming video